The Effect of Exercises by Changing Positions According to Distance Style on The Development of Speed – Strength and Its Relationship with Youth Soccer Players - Hashim, Mohammed; Naji, Diaa (Journal of Physical Education, 2023)
The research aimed at using exercises by changing positions according to distance style and identifying their effect on developing strength – speed and scoring in youth soccer players. The researchers used the experimental method on (18) youth soccer players from Al Sinaa club. The exercises were applied during the main part of a training sessions. The researchers conclude that these exercises by changing positions style develop strength – speed as well as cording skill in youth soccer players. Finally, the researchers recommended using these exercises for developing strength – speed as well as making similar studies and researchers on changing positions according to distance exercises in soccer for other age groups.